2016
DOI: 10.1007/s00439-015-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Rare copy number variants and congenital heart defects in the 22q11.2 deletion syndrome

Abstract: The 22q11.2 deletion syndrome (22q11DS; velocardiofacial/DiGeorge syndrome; VCFS/DGS; MIM #192430; 188400) is the most common microdeletion syndrome. The phenotypic presentation of 22q11DS is highly variable; approximately 60–75 % of 22q11DS patients have been reported to have a congenital heart defect (CHD), mostly of the conotruncal type, and/or aortic arch defect. The etiology of the cardiac phenotypic variability is not currently known for the majority of patients. We hypothesized that rare copy number var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 54 publications
5
63
0
4
Order By: Relevance
“…Recent evidence suggests a role for additional genetic variants that modify risk for congenital heart defects in some patients with the deletion [22]. Conversely, other studies have found no evidence of an increase in novel genome-wide CNVs in patients with the 22q11.2 deletion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests a role for additional genetic variants that modify risk for congenital heart defects in some patients with the deletion [22]. Conversely, other studies have found no evidence of an increase in novel genome-wide CNVs in patients with the 22q11.2 deletion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with a presumed 22q11.2 deletion were recruited from 22 international sites (Table S1) and provided DNA samples that were genotyped using the Affymetrix Genome-Wide Human SNP Array 6.0 at the Albert Einstein College of Medicine (13). Informed consent was obtained from all subjects and/or their legal guardian.…”
Section: Methodsmentioning
confidence: 99%
“…A goal of the International 22q11.2DS Brain and Behavior Consortium (IBBC) (12) is to discover additional genetic factors that contribute to the high risk for schizophrenia in the 22q11.2DS population. Emerging research suggests that additional rare CNVs elsewhere in the genome may shape the expression of cardiac phenotypes associated with 22q11.2DS (13). In the current study, we used high-resolution genome-wide microarrays and proven CNV detection methods (14) to identify rare CNVs that may be involved in the expression of schizophrenia in 22q11.2DS.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most compelling theories considers the influence of the anomalies in genes from the intact 22q11.2 region, as well as additional modifying variants located outside the 22q11.2 region, involving both proteincoding genes and regulatory mechanisms (Goldmuntz et al, 2009). For example, studies evaluating common and rare copy number variants and single nucleotide polymorphisms (SNPs), found that duplications of the glucose transporter gene SLC2A3 have been demonstrated to increase the risk of CHD in patients with 22q11.2DS (Mlynarski et al, 2015, 2016). Another study suggested that rare deleterious SNPs in histone modification-related genes might modify the cardiovascular phenotype in 22q11.2DS (Guo et al, 2015).…”
Section: Genes and Pathogenesis Of The Cardiovascular Phenotypementioning
confidence: 99%